The Role of Digital Financial Literacy and Organizational Cultureon Employee Performance with Financial Information systemas a Mediation variable, the Locus in Kodam IV/Diponegoro - Trisna Wulandari; Fulien Surjana (Universitas 17 Agustus 1945 Semarang, 2026)
This study aims to analyze the influence of Digital Financial Literacy and Organizational Culture on Employee Performance with Financial Information Systems as a mediating variable in Kodam IV/Diponegoro. Using an explanatory quantitative approach, data was collected through a survey of TNI and civil servant personnel who handle financial administration (purposive sampling) and analyzed using SmartPLS. The test results show that Digital Financial Literacy has a positive and significant effect directly on employee performance. On the other hand, Organizational Culture does not have a significant direct effect on performance, but has been proven to have a positive and significant impact on the effectiveness of the Financial Information System. The key findings of this study confirm the strategic position of the Financial Information System which functions as a full mediator for the Organizational Culture in improving performance, as well as being the strongest determinant factor. The implications of this study suggest a priority on strengthening the reliability of the system and the digital competence of personnel in order to realize transparent and accountable defense governance.